Distinct impacts of fat and fructose on the liver, muscle, and adipose tissue metabolome: An integrated view - Meneses, Maria João; Sousa-Lima, Inês; Jarak, Ivana; Raposo, João F.; Alves, Marco G.; Macedo, Maria Paula (Frontiers in Endocrinology, 2022)
Objective: In the last years, changes in dietary habits have contributed to the increasing prevalence of metabolic disorders, such as non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM). The differential burden of lipids and fructose on distinct organs needs to be unveiled. Herein, we hypothesized that high-fat and high-fructose diets differentially affect the metabolome of insulin-sensitive organs as the liver, muscle, and different adipose tissue depots. Methods: We have studied the impact of 12 weeks of a control (11.50% calories from fat, 26.93% from protein and 61.57% from carbohydrates), high-fat/sucrose (HFat) or high-fructose (HFruct) feeding on C57Bl/6J male mice. Besides glucose homeostasis, we analyzed hepatic levels of glucose and lipid metabolism-related genes and the metabolome of the liver, the muscle and white (WAT) and brown adipose tissue (BAT) depots. Results: HFat diet led to a more profound impact on hepatic glucose and lipid metabolism than HFruct, with mice presenting glucose intolerance, increased saturated fatty acids and no glycogen pool, yet both HFat and HFruct presented hepatic insulin resistance. HFat diet promoted a decrease in glucose and lactate pools in the muscle, and an increase in glutamate levels. While HFat had alterations in BAT metabolites that indicate increased thermogenesis, HFruct led to an increase of betaine, a protective metabolite against fructose-induced inflammation. Conclusions: Our data illustrate that HFat and HFruct have a negative but distinct impact on the metabolome of liver, muscle, WAT and BAT.